Factors Affecting Teacher Performance - Wulan, Sarah (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2024)
The literature study research methodology was used in this research. Experts including Gibson, Campbell, Mathis, and Jackson explain the theory of performance factors. Next, a search was carried out using relevant published research findings to evaluate and convey research findings to strengthen previously existing theories. It can be concluded that there are two categories that can be used to group factors that influence teacher performance: internal factors, namely elements that come from the teacher. Apart from that, there are external factors—namely elements that cannot be controlled. Family history, talents, social experiences, demographics, knowledge, self-confidence, drive, personality, role perception, attitude, job happiness, and each person's level of commitment and responsibility are examples of internal factors. The following are examples of external factors: organizational factors (job design, reward structure, organizational structure, and leadership); team factors (quality of support and enthusiasm provided); and leadership factors (the quality of encouragement, enthusiasm, direction, and support provided by managers and Team Leaders). offered by teammates in one team, mutual trust between teammates, cohesiveness and closeness of teammates), contextual factors (pressure and changes in the external environment), system factors (work systems, work facilities, or infrastructure provided by the organization, organizational processes, and performance culture in organizations).